KULISUSU LANGUAGE MAINTENANCE IN TEENAGER GROUP ON EREKE: SOSIOLINGUISTIC STUDY - La Ino Mbangi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
Abstract This article is discusses about the survival of Kulisusu language at the age of adolescence in Ereke Town of North Buton district. A focus of this research is about teenagers age between 17-20 years. The point of problems in this research is the family, association, education, government, transactions, neighbors, religion, culture, art. In this research the approach used is sociolinguistic approach. In this case, the approach (approach) of sociology, ie the study of language in the social context, which studies is the behavior of groups rather than individual. In analyzing the data is done by calculating the percentage following the calculation pattern, that is the calculation built on the number of incoming answers) The results are found kulisusu language Based on the analysis shows the category of adolescents and adults Kulisusu language tendency is in the medium category on the side still at last Keywords: sosiolinguistik kertausu defense